Nanomedicine-mediated prevention of inflammatory monocytes infiltration ameliorate ovalbumin-induced allergic rhinitis in mouse model - Xiaofeng Gu; Feng Xiao; Wenmin Lu; Ying Xu; Xia Li; Chenjie Yu; Xinyan Cui (Taylor & Francis Group, 2020)
Th2 immune cells infiltration into nasal mucosa is one of the characters of allergic rhinitis (AR). We aimed to explore whether inhibition of Th2 immune cells infiltration would attenuate AR progression. AR mouse model was established by i.p. injection of ovalbumin (OVA). The infiltrated immune cells into nasal lavage fluid were detected by flow cytometry. Cytokine concentration in serum was determined by ELISA. AR mice symptoms were indicated by the number of sneezing and nasal rubbing events. In AR mice, CCL2 expression levels and CD45+CD11b+Ly6Chi inflammatory monocytes cells significantly increased as compared with control mice. CCL2 siRNA encapsulated nanoparticles (NPsiCCL2) prevent CCL2 expression and inflammatory monocytes infiltration in AR mice. NPsiCCL2 treatment dramatically decreased the number of sneezing and nasal rubbing events in AR mice. Moreover, NPsiCCL2 treatment attenuated serum OVA-specific IgE, OVA-specific IgG1 and histamine levels. Mechanically, NPsiCCL2 treatment attenuates AR symptoms via inhibiting Th2 cytokine (IL-4, IL-5 and IL-13) production. Nanomedicine-mediated prevention of inflammatory monocytes infiltration ameliorates ovalbumin-induced allergic rhinitis in mouse model.